2018
DOI: 10.12681/jhvms.15608
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of serum cardiac biomarkers in sheep with acute lactic acidosis

Abstract: In this study we investigated the changes of cardiac injury biomarkers in serum samples from 200 sheep with acute ruminal lactic acidosis (ARLA) and 50 healthy controls belonging to the Ghezel breed. After clinical examination and recording of vital signs (heart rate, respiratory rate, rectal temperature and hydration status), rumen fluid and venous blood samples were collected. The pH of rumen fluid was determined using a paper tape pH-meter and lactic acid concentration of serum was measured using a commerci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 21 publications
(27 reference statements)
0
4
0
Order By: Relevance
“…In horses with colic undergoing emergency abdominal surgery, increases in L-lactate and cTnI were observed, and both were higher in the animals that did not survive surgical treatment [27]. In sheep with acute ruminal acidosis, hyperlactatemia and a significant negative correlation (r = -0.85; P = 0.004) were reported between ruminal pH and serum L-lactate levels, as well as elevation in CK-MB and cTnI [13]. In humans, blood L-lactate has been shown to be a marker of risk stratification and mortality in patients with heart disease [18].…”
Section: Discussionmentioning
confidence: 94%
“…In horses with colic undergoing emergency abdominal surgery, increases in L-lactate and cTnI were observed, and both were higher in the animals that did not survive surgical treatment [27]. In sheep with acute ruminal acidosis, hyperlactatemia and a significant negative correlation (r = -0.85; P = 0.004) were reported between ruminal pH and serum L-lactate levels, as well as elevation in CK-MB and cTnI [13]. In humans, blood L-lactate has been shown to be a marker of risk stratification and mortality in patients with heart disease [18].…”
Section: Discussionmentioning
confidence: 94%
“…Although the serum CK-MB activity and serum cTnI concentration were higher in the CG and TG, respectively, these cardiac injury biomarkers remained within the normal range, not varying after induction of the disease, disagreeing with the reports of Fartashvand; Haji-Sadeghi (2017), Kirbas et al (2014b), and Joshi et al (2017) who showed elevation in cTnI and CK-MB in sheep and goats clinically affected by RLA, suggesting some degree of myocardial injury in these animals which presented severe clinical manifestations and a high mortality rate. Possible reasons for the occurrence of cardiac damage in ruminal acidosis include: metabolic acidosis; severe dehydration; oxidative stress, with excessive production of reactive oxygen species; endotoxemia; increased synthesis and release of inflammatory cytokines (CHALMEH et al, 2014;FARTASHVAND;HAJI-SADEGHI, 2017;JOSHI et al, 2017;KATRUKHA, 2013;KIRBAS et al, 2014aKIRBAS et al, , 2014b). Fartashvand; Haji-Sadeghi (2017) indicated a relation between cTnI and the prognosis in ruminal acidosis, finding that animals with more critical ruminal pH values presented the highest concentrations of this biomarker and died acutely.…”
Section: Discussionmentioning
confidence: 99%
“…It is hypothesized that acid-base and electrolyte disturbances and secondary complications associated with RLA cause cardiovascular injury. Recently, cardiac injury biomarkers have been used in studies seeking to evaluate the association between myocardial injury and ruminal acidosis in small ruminants (FARTASHVAND; HAJI-SADEGHI, 2017;JOSHI et al, 2017;KIRBAS et al, 2014a) however, this relationship is still not fully understood.…”
Section: Introductionmentioning
confidence: 99%
“…Lungs are characterized by congestion with severe diffuse edema (Lira et al, 2013). Liver failure, muscular weakness, and further rhabdomyolysis are aggravated due to recumbency during ARA (Constable, 2010;Fartashvand and Haji-Sadeghi, 2018).…”
Section: Pathoanatomical Lesionsmentioning
confidence: 99%